2011
DOI: 10.5194/acpd-11-19029-2011
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Air quality trends in Europe over the past decade: a first multi-model assessment

Abstract: We discuss the capability of current state-of-the-art chemistry and transport models to reproduce air quality trends and inter annual variability. Documenting these strengths and weaknesses on the basis of historical simulations is essential before the models are used to investigate future air quality projections. To achieve this, a coordinated modelling exercise was performed in the framework of the CityZEN European Project. It involved six regional and global chemistry-transport models (Bolchem, Chim… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 58 publications
2
42
0
2
Order By: Relevance
“…Many studies qualitatively match the direction of observed trends in aerosol but underestimate both absolute concentrations and the magnitude of observed trends (Berglen et al, 2007;Colette et al, 2011;Koch et al, 2011;Chin et al, 2014). Leibensperger et al (2012) used the chemical transport model (CTM) GEOS-Chem to evaluate aerosol trends over the USA at decadal time slices and found that sulfate but not BC was represented well by the model.…”
Section: S T Turnock Et Al: Modelled and Observed Changes In Europmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies qualitatively match the direction of observed trends in aerosol but underestimate both absolute concentrations and the magnitude of observed trends (Berglen et al, 2007;Colette et al, 2011;Koch et al, 2011;Chin et al, 2014). Leibensperger et al (2012) used the chemical transport model (CTM) GEOS-Chem to evaluate aerosol trends over the USA at decadal time slices and found that sulfate but not BC was represented well by the model.…”
Section: S T Turnock Et Al: Modelled and Observed Changes In Europmentioning
confidence: 99%
“…Leibensperger et al (2012) used the chemical transport model (CTM) GEOS-Chem to evaluate aerosol trends over the USA at decadal time slices and found that sulfate but not BC was represented well by the model. A multimodel assessment of aerosol trends in Europe over the last decade showed models successfully simulate observed negative trends in PM 10 but fail to reproduce the positive trends observed at some locations and typically underestimate absolute concentrations (Colette et al, 2011). Observed reductions in sulfate over Europe have also been underestimated by other studies (Berglen et al, 2007;Koch et al, 2011).…”
Section: S T Turnock Et Al: Modelled and Observed Changes In Europmentioning
confidence: 99%
“…15.7 and discussed in more detail by Tørseth et al (2012), the trends in SO X , NO X and NH 3 emissions are generally reflected in the measurements, with the exceptions of SO 4 2− (discussed above) and NO 3 − . Colette et al (2011) also found robust trends in NO 2 over the past ten years, with the majority of monitoring stations in Europe showing reductions of about 50-60 % over this period. The concentrations of total airborne NO 3 − decreased on average by only 8 %.…”
Section: Sulphur and Nitrogenmentioning
confidence: 72%
“…Jenkin 2008). Colette et al (2011) presented trends in O 3 (as well as NO 2 and PM 10 ) over the past ten years. They found that (as expected) the trends in O 3 reflect trends in NO 2 .…”
Section: Ozonementioning
confidence: 97%
“…16.9) a corresponding reduction in O 3 concentration is not observed (Jonson et al 2006;EEA 2009EEA , 2012Tørseth et al 2012;Wilson et al 2012). Models also generally struggle to reproduce some of the observed trends (Solberg et al 2005;Jonson et al 2006;Colette et al 2011;Wilson et al 2012;Parrish et al 2014). Likely reasons include increased (Fagerli et al 2012) background (hemispheric) O 3 level-observational evidence suggests that the increase in background O 3 roughly doubled from 1950 to 2000 and then levelled off (Logan et al 2012;Derwent et al 2013;Oltmans et al 2013;Parrish et al 2013).…”
Section: Air Pollutionmentioning
confidence: 98%